Pengaruh Skeptisisme Profesional dan Kompetensi Auditor terhadap Audit Judgment dengan Moral Reasoning sebagai Variabel Moderasi - Dewa Ayu Arita Sri Patni; I Nyoman Gede Arya Diatmika (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Audit judgment is an auditor’s professional decision that plays a critical role in maintaining the quality and credibility of audit outcomes; however, in practice it remains influenced by various individual auditor factors. This study aims to examine the effects of professional skepticism and auditor competence on audit judgment, with moral reasoning as a moderating variable. A quantitative approach was employed by distributing questionnaires to 70 auditors working in Public Accounting Firms in Bali Province, selected using purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that auditors’ professional skepticism does not have a significant effect on audit judgment, whereas auditor competence has a positive and significant effect on audit judgment. In addition, moral reasoning is found to moderate the relationship between professional skepticism and audit judgment as well as the relationship between auditor competence and audit judgment. These findings suggest that moral considerations play an important role in strengthening audit decision-making, particularly when combined with auditors’ competence and professional attitudes. Theoretically, this study supports Attribution Theory and Kohlberg’s Moral Development Theory in explaining how individual factors and moral considerations shape audit judgment that is integrity-driven and oriented toward the public interest.